2019
DOI: 10.36366/frontiers.v31i2.453
|View full text |Cite
|
Sign up to set email alerts
|

Gender x Culture: A pilot project exploring the study abroad experiences of trans and gender expansive students

Abstract: As gender is socially constructed, gender a ttitudes, expressions, expectations and identities may differ based on their sociocultural contexts. This project sought to understand interactions between gender and culture through the experiences of three undergraduate study abroad students who are tra ns and/or gender expansive. Utilizing the thematic analysis method, data from a focus group and individual follow up interviews were analyzed ; seven themes emerged from the data collected. As study abroad has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…Articles Eight articles in the StAR Database met inclusion criteria, of which seven were new and one (Michl et al, 2019) had already been identified through the focused electronic search. At this point, 10 articles met inclusion criteria between the two searches.…”
Section: Articles Identified Via Area Databasementioning
confidence: 99%
See 2 more Smart Citations
“…Articles Eight articles in the StAR Database met inclusion criteria, of which seven were new and one (Michl et al, 2019) had already been identified through the focused electronic search. At this point, 10 articles met inclusion criteria between the two searches.…”
Section: Articles Identified Via Area Databasementioning
confidence: 99%
“…LGBT+ identity, but not necessarily a direct focus on LGBT+ participants. Five of the thirteen studies directly focused on LGBT+ as the central component (Brown, 2014;Bryant & Soria, 2015;Michl et al, 2019;Mnouer, 2020;Donahue & Wise, 2021). Six studies had LGBT+ participants but did not focus directly on LGBT+ identity as their main findings (Kimble et studies' foci and/or how the academic content relates to health and identity issues surrounding queer communities speaks to how the scholars centralize notions of LGBT+ identity.…”
Section: Study Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly studied wellbeing outcomes included psychological health, wellbeing, and adaptation (e.g., Fanari & Segrin, 2021;Thomas & Waugh, 2020); emotional resilience and grit (e.g., Harrison & Voelker, 2008;Zayac et al, 2021); sense of belonging (e.g., Teranishi & Hannigan, 2008); and alcohol use, risk behavior, and sexual violence (e.g., Pedersen et al, 2009;Pedersen et al, 2020). More recently published studies have explored aspects of identity beyond cultural identity, including trans and gender expansive identity (Michl et al, 2019) and masculinity (Simpson & Bailey, 2021).…”
Section: Wellbeing Outcomesmentioning
confidence: 99%
“…LGBT+ Results from the current synthesis warrant further investigation of study abroad participants who self-identify within the broad spectrum of queer (queer functioning here as an umbrella category that is inclusive of the multiplicity of LGBT+ identities contained therein, but disparate from Queer as a recognized self-identification; Jagose & Genschel, 1996). Of the included studies, Michl et al (2019) was the primary article that focused on trans (i.e., queer, gender-non-conforming, non-binary, and transgender) identification in study abroad and the sole article in the AREA Database that touches on the wider LGBT+ experience, while others either represented an LGBT identity in some capacity or focused on a social topic relevant to the queer community (e.g., HIV/AIDS; Diesel et al, 2013). Without a base of research on LGBT+ study abroad participants, practitioners are lacking evidence-based programs to enhance LGBT+ students' experiences and outcomes, especially given the unique needs of these students; thus, we recommend experts conduct a focused literature review on LGBT+ students abroad to catalyze further research.…”
Section: Students Of Colormentioning
confidence: 99%